RESEARCH OF AREAS OF DANGEROUS COMBINATION "HEIGHT - FLIGHT SPEED" FOR GYROPLANE - V. A. Ivchin (Научный вестник МГТУ ГА, 2015)
The article conducted research, using the simulation PFD stand to determine dangerous combination "height - flight speed" for gyroplane and developed preliminary recommendations on the actions of the pilot in the event of failure of the gyroplane power plant.